Equal size, equal role? Interdependence between the euro area and the United States - Michael Ehrmann; Marcel Fratzscher (European Central Bank (ECB), 2004)
This paper investigates whether the degree and the nature of economic and monetary policy interdependence between the United States and the euro area have changed with the advent of EMU. Using real-time data, it addresses this issue from the perspective of financial markets by analysing the effects of monetary policy announcements and macroeconomic news on daily interest rates in the United States and the euro area. First, the paper finds that the interdependence of money markets has increased strongly around EMU. Although spillover effects from the United States to the euro area remain stronger than in the opposite direction, we present evidence that US markets have started reacting also to euro area developments since the onset of EMU. Second, beyond these general linkages, the paper finds that certain macroeconomic news about the US economy have a large and significant effect on euro area money markets, and that these effects have become stronger in recent years. Finally, we show that US macroeconomic news have become good leading indicators for economic developments in the euro area. This indicates that the higher money market interdependence between the United States and the euro area is at least partly explained by the increased real integration of the two economies in recent years.
Keywords: E43; E52; F42; 330; announcements; euro area; interdependence; money markets; news; real-time data; United States